The Effect of Think, Talk, Write (TTW) Strategy on The Writing Descriptive Text Ability of SMK Students - Annisa, Fitri; Supriusman, Supriusman; Masyhur, Masyhur (Journal of Educational Sciences, 2025)
This study aims to find the effect of Think, Talk, Write (TTW) strategy on the writing descriptive text ability of SMK students. The study used a quasi-experimental method with two groups: an experimental class taught using the TTW strategy and a control class using the conventional method. The data collection instrument was a descriptive writing test conducted before (pre-test) and after (post-test) treatment, with an assessment based on the Arthur Hughes rubric. The data were analyzed using independent sample t-test. The results showed that the TTW strategy had a significant effect on students' writing ability. The average value of the final test of the experimental class reached 87.17, higher than the control class which obtained an average of 76.25. This difference was also confirmed through a statistical test with a p value <0.001, which showed that students taught with the TTW strategy experienced a greater improvement in writing ability than students taught with the conventional method. The TTW strategy helps students to think critically, discuss, and organize their writing in a more structured way, thus improving the quality of the text they produce. The findings support the effectiveness of TTW in improving descriptive writing skills. This study recommends the use of TTW strategy in writing learning to create a more collaborative and in-depth learning process. Future researchers are expected to explore the application of TTW on different text types or populations.